Durability of Diesel Engine Using Biolubricant and the Effect on Performance - Beny Cahyono; Aguk Zuhdi M. Fathallah; Aridhanka Youri Al Kahfi (International Journal of Marine Engineering Innovation and Research, 2021)
Environmental needs to reduce pollution caused by used lubricants from mineral oil encourage the development of biolubricant. One of the biolubricant raw materials from plants available in the environment is the castor plant (ricinus communis). The biggest composition in castor oil is ricinoleic acid which can be used in the manufacture of biolubricants. The purpose of this study was to study the physical properties of biolubricants from castor oil, to compare the properties of biolubricants and mineral lubricants after conducting a diesel engines durability test, and comparing performance between both lubricants during durability test. Experiment were carried out on the Dongfeng R180 diesel engine using Pertamina Dexlite fuel and mineral oil Pertamina Mesran B SAE 40 as a comparison. The results of biolubricant properties test (kinematic viscosity, viscosity index, pour point, flash point, and total alkali number) were obtained according to the flash point value not fulfilling the Minister of Energy and Mineral Resources Regulation regarding standard. From properties between biolubricants and mineral lubricants after a 200-hour endurance test there is properties change in both lubricants. Increase the value of viscosity, total number of base, and  flash point because it contains water in the biolubricant causing oxidation. The iron content of the biolubricants after the endurance test is greater than mineral lubricants. However, the aluminum content in biolubricants is smaller when compared to biolubricants. From the performance test obtained SFOC which is produced when using mineral oil at peak torque is 3.1% lower than compared when using biolubricants. The average SFOC in the value condition when using biolubricants is 2.3% lower than using biolubricants. The average power when using mineral lubricants is 0.72% lower when compared to biolubricants and the resulting torque is 0.23% lower when compared to using biolubricants.